Enhancing the aesthetic aspect of the solar systems used as facades for building by designing multi-layer optical coatings - AL-Assadi, Zainab I.; AL-Assadi, Fawzia Irhayyim (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The design of zero-energy buildings can be depending on the effective integration of solar energy systems with building envelopes, where these systems save heat and electricity as well as enhance the aesthetic aspect of the facades. In this paper, the aspects related to the effective integration of buildings with solar energy systems (solar cells and collectors) will be discussed, as well as enhancing the aesthetic aspect of the facades, and since solar energy systems are visible to everyone, their design must adapt to the building structure and the surrounding environment. Solar energy system designers, architects, physicists and other contributors to building energy envelopes must consider the comprehensive concept of it, where buildings are part of the human and social environment and in close relationship with the natural environment, through the use of thin films technology through the design of multi-layers colored optical coatings covering solar panels for building facades. Accordingly, the energy sector should be seen as an area of aesthetic creativity. Two dielectric materials were used, the first is ThF4 with a high refractive index (1.5143) and the second is LiF with a low refractive index (1.393) and for several odd layers, starting from 3 layers and up to 21 layers and for a thicknesses of a quarter wavelength. The design Air/L/H/Glass was applied by the Mat Lab program for the seven colors of the spectrum, So, the aim of this research is determined in designing colored optical coatings for solar systems that enhance the aesthetic aspect of building facades, as well as generating thermal and electrical energy needed to operate the buildings and to find out which color has the best visible reflectivity and solar transmittance better than the rest of the spectrum, all the results exhibit that yellow color has the higher visible reflectivity and higher merit factor, so it is consider the most efficient color for coloring the solar systems than the rest of colors spectrum.